Patterson-Sullivan distributions of finite regular graphs - Arends, Christian; Palmirotta, Guendalina (arXiv:2603.09779)
On finite regular graphs, we construct Patterson-Sullivan distributions associated with eigenfunctions of the discrete Laplace operator via their boundary values on the phase space. These distributions are closely related to Wigner distributions defined via a pseudo-differential calculus on graphs, which appear naturally in the study of quantum chaos. Using a pairing formula, we prove that Patterson-Sullivan distributions are also related to invariant Ruelle distributions arising from the transfer operator of the geodesic flow on the shift space. Both relationships provide discrete analogues of results for compact hyperbolic surfaces obtained by Anantharaman-Zelditch and by Guillarmou-Hilgert-Weich.

Digital Fascism and Digital Capitalism - Fuchs, Christian (Philosophy & Social Criticism)

Symbolic haunting: first-generation university students’ limited sense of entitlement - Lin-Januszewski, Liang-Wen (British Journal of Sociology of Education)

Keuchen, Marion/ Lindemeyer, Sabine: Demokratiebildung anhand eines (schul-)seelsorglichen Rituals im Rahmen der Lehramtsausbildung - Keuchen, Marion; Lindemeyer, Sabine (Seelsorge im Lebensraum Schule. Ökumenische Perspektiven)

Influence of deposition temperature and thickness of ALD-TiO2 on planar perovskite solar cell performance - Qudsia, Syeda; Weiss, Alexander; Sirkiä, Saara; Wang, Fuzeng; Rosqvist, Emil; Los Arcos, Teresa De; Weinberger, Christian; Halme, Janne; Kemell, Marianna; Smått, Jan-Henrik (Applied Surface Science)
In perovskite solar cells (PSCs), electron transport layers (ETLs) play an important role in the selection and transport of electrons. Understanding the properties of these layers in relation to device performance is essential for optimizing solar cell efficiency and enabling their integration into emerging architectures, such as flexible solar cells. Here, we deposited TiO2 at different thicknesses using atomic layer deposition (ALD), a technique well-suited for producing uniform and pinhole-free films. The crystal structure of the layers was controlled by depositing the films at three different temperatures: 150 °C, 250 °C, and 350 °C. The layers were characterized in detail to determine the morphology (by atomic force microscopy), surface composition (by X-ray photoelectron spectroscopy) and the crystal structure (by X-ray diffraction). The TiO2 layers were then incorporated as ETLs in planar perovskite solar cells to evaluate their influence on device performance. Higher deposition temperatures led to improvements in device fill factor and open-circuit voltage, leading to more efficient solar cells. Notably, the best device performance for the ALD-TiO2 layers was achieved with films deposited at 250 °C.
Keywords: Titanium dioxide; Atomic layer deposition; Electron transport layer; Perovskite solar cells

Vom „Push the Keys“ zum „Touch the Screen“? Eine Spurensuche zur Konkurrenz der Dinge im Musikunterricht. - Godau, Marc (Beiträge empirischer Musikpädagogik)
Der Beitrag untersucht die Einführung von iPads im Musikunterricht einer Sekundarschule aus einer soziomaterialen Perspektive. Auf der Grundlage einer mehrjährigen Begleitung wird mit Verfahren der Situationsanalyse aufgezeigt, wie die Digitaltechnologien – insbesondere die App GarageBand – in bestehende Fachkulturen, Dingordnungen und Unterrichtsroutinen eingebettet werden. Die Analyse offenbart, wie im Musikunterricht der Digitalisierungsprozess oft an alten Dingen, vertrauten Routinen und fachimmanenten Ideologien, wie dem Klaviozentrismus und einer Liveness-Norm, scheitert. Zugleich ergänzt ein alternatives Verständnis unterrichtlichen Musiklernens das handwerkliche Reproduzieren und Selbstüberwinden in Präsenzdarbietungen um die Klangarbeit beim explorativ-selbstständigen Erfinden und Produzieren präziser Aufnahmen. Die Ergebnisse werden hinsichtlich der Debatten um Digitalisierung in Schule und Musikunterricht diskutiert.
Keywords: Digitalisierung; GarageBand; Tablet-Klassen; Fachkultur; Situationsanalyse

Institutionalisierung der schulpraktischen Ausbildung im Ausland: Empirische Befunde zu Entwicklungen und Möglichkeiten neuer Wege in der Lehrer*innenbildung - Spiekenheuer, Mara; Freitag, Christine; Koch, Lea (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- Und Professionsentwicklung.)

Chancen und Herausforderungen des Krisenbegriffs zur Untersuchung historischen Lernens im bilingualen Geschichtsunterricht. Werkstattbericht eines Dissertationsprojekts - Pilz, Franziska (Geschichtslernen in Zeiten der Krise)

Evi:P - Evaluationsinstrument für eine partizipative und inklusive Praxis in der Kindertagesbetreuung - Albers, Timm; Meusel, Sarah

Vollständige Bestimmung der akustischen Materialparameter von Polymeren II - Dreiling, Dmitrij; Itner, Dominik; Birk, Carolin; Gravenkamp, Hauke; Henning, Bernd
In diesem Forschungsprojekt wurde ein Messverfahren zur Bestimmung akustischer Materialparameter von Polymeren im Ultraschallfrequenzbereich entwickelt. Das Verfahrens sollte, die üblichen standardisierten Prüfmethoden erweitern, die bislang primär im quasistatischen oder niederfrequenten Bereich eingesetzt wurden. Im Gegensatz zu bestehenden Verfahren wie dem Zeitstandversuch oder der Dynamisch Mechanischen Analyse (DMA) nach [DIN6721] sollte die neue Methode eine nicht-invasive Charakterisierung der (visko-)elastischen Materialparameter im Frequenzbereich von 0,75 MHz bis 2,5 MHz ermöglichen. Das entwickelte Ultraschallmesssystem arbeitet nach dem Puls Echo-Prinzip und kann eine räumlich segmentierte, ringförmige Anregung erzeugen. Die Bestimmung der frequenzabhängigen Materialparameter geschieht hierbei über ein inverses Verfahren. Die Ergebnisse des Projekts zeigen, dass die Segmentierung der Anregung, die Geometrie der Probe sowie das Puls-Echo-Messprinzip die Messergebnisse sowie die Sensitivität gegenüber Scherparametern wesentlich beeinflussen. Im Rahmen des Projektes wurde auch eine statistische Auswertung des Optimierungsverfahrens hinsichtlich transversal-isotroper Materialsymmetrie mit Rayleigh-Dämpfung durchgeführt. Die Ergebnisse zeigen, dass das entwickelte Verfahren gute Konvergenzeigenschaften aufweist und sich durch verbesserte Robustheit auszeichnet.
Keywords: Materialcharakterisierung; Polymer; Inverses Problem; Ultraschall; Optimierung

A gradient-damage model for amorphous glassy polymers: Consistent formulation of viscoplasticity and damage evolution in a micromorphic framework - Hamdoun, Ayoub; Mahnken, Rolf; Ostwald, Richard (European Journal of Mechanics / A Solids)

Prädiktoren der persönlichen Verpflichtung in Eltern-Kind-Beziehungen im Erwachsenenalter - Schönert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie)

Discrete Diffusion-Based Model-Level Explanation of Heterogeneous GNNs with Node Features - Das, Pallabee; Heindorf, Stefan (Proceedings of the ACM Web Conference 2026 (WWW ’26))
Many real-world datasets, such as citation networks, social networks, and molecular structures, are naturally represented as heterogeneous graphs, where nodes belong to different types and have additional features. For example, in a citation network, nodes representing "Paper" or "Author" may include attributes like keywords or affiliations. A critical machine learning task on these graphs is node classification, which is useful for applications such as fake news detection, corporate risk assessment, and molecular property prediction. Although Heterogeneous Graph Neural Networks (HGNNs) perform well in these contexts, their predictions remain opaque. Existing post-hoc explanation methods lack support for actual node features beyond one-hot encoding of node type and often fail to generate realistic, faithful explanations. To address these gaps, we propose DiGNNExplainer, a model-level explanation approach that synthesizes heterogeneous graphs with realistic node features via discrete denoising diffusion. In particular, we generate realistic discrete features (e.g., bag-of-words features) using diffusion models within a discrete space, whereas previous approaches are limited to continuous spaces. We evaluate our approach on multiple datasets and show that DiGNNExplainer produces explanations that are realistic and faithful to the model's decision-making, outperforming state-of-the-art methods.

Navigating the dual nature: do explainers adapt to explainee interests when explaining technical artifacts - Lutz, Terfloth; Buhl, Heike M.; Lohmer, Vivien; Kern, Friederike; Schaffer, Michael E.; Schulte, Carsten (International Journal of Technology and Design Education)

Von Baumdaten zu Datenwäldern. Eine Umweltgeschichte der Informationsverarbeitung im Ausklang des langen 19. Jahrhunderts - Schmitt, Martin (Rechnen, Zeichnen, Reden Zur Geschichte der Datenverarbeitung im langen 19. Jahrhundert)
Keywords: Umweltgeschichte; 19. Jahrhundert; Deutschland; Forstwirtschaft; Konrad Zuse; Datenverarbeitung; Umweltdaten

When prediction replaces explanation: A threat to psychological science - Knauff, Markus; Butz, Martin V.; Kaup, Barbara; Kunde, Wilfried; Scharlau, Ingrid (psyarxiv)
Keywords: explainability; explanation; prediction

Predicting states of understanding in explanatory interactions using cognitive load-related linguistic cues - Wang, Yu; Türk, Olcay; Grimminger, Angela; Buschmeier, Hendrik (Proceedings of the 15th Language Resources and Evaluation Conference)
We investigate how verbal and nonverbal linguistic features, exhibited by speakers and listeners in dialogue, can contribute to predicting the listener's state of understanding in explanatory interactions on a moment-by-moment basis. Specifically, we examine three linguistic cues related to cognitive load and hypothesised to correlate with listener understanding: the information value (operationalised with surprisal) and syntactic complexity of the speaker's utterances, and the variation in the listener's interactive gaze behaviour. Based on statistical analyses of the MUNDEX corpus of face-to-face dialogic board game explanations, we find that individual cues vary with the listener's level of understanding. Listener states (‘Understanding’, ‘Partial Understanding’, ‘Non-Understanding’ and ‘Misunderstanding’) were self-annotated by the listeners using a retrospective video-recall method. The results of a subsequent classification experiment, involving two off-the-shelf classifiers and a fine-tuned German BERT-based multimodal classifier, demonstrate that prediction of these four states of understanding is generally possible and improves when the three linguistic cues are considered alongside textual features.

The Intersection Distribution: New Results and Perspectives - Klawuhn, Lukas-André Dominik; Huczynska, Sophie; Paterson, Maura (Finite Fields and Their Applications)
Intersection distribution and non-hitting index are concepts introduced recently by Li and Pott as a new way to view the behaviour of a collection of finite field polynomials. With both an algebraic interpretation via the intersection of a polynomial with a set of lines, and a geometric interpretation via a (q+1)-set possessing an internal nucleus, the concepts have proved their usefulness as a new way to view various long-standing problems, and have applications in areas such as Kakeya sets. In this paper, by exploiting connections with diverse areas including the theory of algebraic curves, cyclotomy and the enumeration of irreducible polynomials, we establish new results and resolve various Open Problems of Li and Pott. We prove geometric results which shed new light on the relationship between intersection distribution and projective equivalence of polynomials, and algebraic results which describe and characterise the degree of Sf - the index of the largest non-zero entry in the intersection distribution of f. We provide new insights into the non-hitting spectrum, and show the limitations of the non-hitting index as a tool for characterisation. Finally, the benefits provided by the connections to other areas are evidenced in two short new proofs of the cubic case.

Einleitung: Alles fließt - Spener, Anna Maria (WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien. Sammelband zur fünften studentischen Tagung des Fachbereichs Komparatistik an der Universität Paderborn)

Nasses Land: Wetlands als relationale Räume gegenhegemonialer Wissensproduktion in der künstlerischen Forschung - Spener, Anna Maria (WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien)